2009
DOI: 10.1049/iet-cta.2008.0148
|View full text |Cite
|
Sign up to set email alerts
|

On the simultaneous state and unknown input estimation of complex systems via a multiple model strategy

Abstract: This paper addresses the analysis and design of unknown input observer in order to provide both state and unknown input estimation of complex systems modelled with the help of a particular class of multiple model. The proposed observer uses the multi-integral strategy successfully employed in the classic linear control theory and known for its robustness properties. The observer design is based on the representation of the system via a multiple model, known as decoupled multiple model. This structure of multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…With P=diag(P 1 , P 2 )>0, (2)-(15), the Schur complement and variable changes defined by (24), we get conditions (26) where ∆ 1i and ∆ 2i are defined by (20). This completes the proof.…”
Section: H -Fault Sensitivity Conditionsmentioning
confidence: 53%
See 2 more Smart Citations
“…With P=diag(P 1 , P 2 )>0, (2)-(15), the Schur complement and variable changes defined by (24), we get conditions (26) where ∆ 1i and ∆ 2i are defined by (20). This completes the proof.…”
Section: H -Fault Sensitivity Conditionsmentioning
confidence: 53%
“…with ∆ 1i and ∆ 2i are defined by (20). Then the estimation error (16) is asymptotically stable with the performance (9).…”
Section: H -Fault Sensitivity Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sequel, this multiple model is called the heterogeneous multiple model. The previously quoted works have illustrated successful implementations of this structure for modelling (Venkat et al, 2003;Vinsonneau et al, 2005;Orjuela et al, 2006), control (Gawthrop, 1995;Gatzke and Doyle III, 1999;Gregorčič and Lightbody, 2000) or state estimation and diagnostic (Kanev and Verhaegen, 2006;Uppal et al, 2006;Orjuela et al 2008;2009) and have shown its relevance. Hence, this kind of multiple model can be used as an interesting alternative to the homogeneous multiple model.…”
Section: R Orjuela Et Almentioning
confidence: 99%
“…This kind of multiple model, initially proposed by Filev (1991), is reported in the literature under several designations, such as the local-state local model network (Gawthrop, 1995), the multiple local models (Gatzke and Doyle III, 1999;Venkat et al, 2003;Vinsonneau et al, 2005), local model networks by blending the outputs (Gregorčič and Lightbody, 2000;, multiple model for models with a non-common state (Kanev and Verhaegen, 2006), the neuro-fuzzy decoupling multiple model scheme (Uppal et al, 2006) and the recently decoupled multiple model (Orjuela et al, 2006;2009). Despite their different names, these approaches share a similar multiple model structure.…”
Section: R Orjuela Et Almentioning
confidence: 99%